Examination of an applicable range for a markerless motion capture system in gait analysis - Sakurai, T.; Okada, H. (ISBS Proceedings Archive (Michigan), 2021)
This study aimed to verify the measurement accuracy of a markerless motion capture system using OpenPose in comparison with the conventional motion capture system using infrared cameras and to discuss an applicable range for the markerless motion capture system. We verified the accuracy of the system by calculating errors in the fundamental parameters of gait analysis. Those errors were 4.42 ± 2.02° in hip angle, 4.26 ± 2.54° in knee angle, and 5.93 ± 4.31° in ankle angle. The verification test revealed that this markerless motion capture system could be readily available, at least in the case of collecting 2D kinematics in the sagittal plane for gait motion.